The Effect of Classical Counseling Guidance Services on Increasing Self-Control of High School Students - Sipahutar, Adelia Putri; Nurhayani, Nurhayani (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2024)
This study aims to examine the influence of classical counseling services on the improvement of self-control among tenth-grade students at SMA Cerdas Murni, Tembung, Percut Sei Tuan District, Deli Serdang Regency. The method used in this research is a quantitative approach with a quasi-experimental design, utilizing a pretest-posttest Nonequivalent Control Group. The study population includes tenth-grade students at SMA Cerdas Murni, and the sample was selected using purposive sampling techniques. The sample consisted of 29 students from class X-4 in the experimental group and 26 students from class X-3 in the control group. The data were obtained from self-control questionnaires filled out by students both before (pretest) and after (posttest) the counseling services were provided. The data source included responses from 55 students who participated in the study. The instrument used is a. Data analysis was carried out using the t-test after normality and homogeneity tests were conducted. The results of the study showed an Asymp.sig (2-tailed) value of 0.001 < 0.05, indicating that the hypothesis is accepted (H1). Classical counseling services were proven to significantly improve students' self-control. Students who received these services showed greater self-control improvement compared to those who did not. This indicates that classical counseling services are effective in helping students enhance their self-control abilities.